Exploring the balance between functionality and aesthetics: an analytical framework and pragmatic consideration of the anthropomorphism of service robots - Xin, Xin; Liu, Wenchao (Frontiers in Psychology, 2025)
The phenomenon of anthropomorphism in service robots has gained significant traction across multiple service industries; however, there remains a lack of a robust theoretical framework that adequately elucidates the preference for anthropomorphic design. Following the systematic review methodology, our findings indicate that the design of service robots necessitates a careful equilibrium between functional capabilities and aesthetic considerations. Central to the concept of anthropomorphism in service robots is the attribution of human-like characteristics, motivations, intentions, and emotions to their perceived or actual behaviors, aimed at enhancing human comprehension of robotic actions and promoting meaningful social interactions. From a design standpoint, anthropomorphism fulfills cognitive requirements while also serving as a mechanism for inductive reasoning. Influential factors in the anthropomorphism of service robots include the activation of human subject knowledge, effectiveness motivation, and social motivation, alongside additional variables such as individual personality traits, contextual elements, developmental phases, and cultural backgrounds, all of which exert a direct impact. The anthropomorphism of service robots has engendered significant considerations regarding human expectations, the perceived intelligence of robots, and the management of anthropomorphic attributes. A thorough investigation into the mechanisms that underpin the anthropomorphic interpretation of service robots, along with the practical implications that emerge, can assist various service organizations in determining the appropriate types and levels of anthropomorphic service robots, while also facilitating customers’ engagement with these robots in a more rational and contextually appropriate manner.